Consumer information in a market for expert services: Experimental evidence - Tim Schneider; Lukas Meub; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
Markets for expert services are characterized by information asymmetries between experts and consumers. We analyze the effects of consumer information, where consumers suffer from either a minor or serious problem and only experts can infer the appropriate treatment. Consumer information is a noisy signal that is informative about a consumer's problem severity. In a laboratory experiment, we show that consumers are generally reluctant to accept expensive treatment recommendations, which is endorsed by good signals and fundamentally changed by bad signals. Experts condition their cheating on a consumer's risk of suffering from a serious problem if they can observe consumer information. Accordingly, experts and low-risk consumers benefit at the expense of more frequently cheated high-risk consumers. Consumer information leads to more appropriate treatments being carried out and thus superior overall welfare. In contrast to our theoretical predictions, this effect does not depend on hiding consumer information for experts.
Keywords: C70; C91; D82; 330; consumer information; credence goods; experts; laboratory experiment